“To me, this illness is the same as nothing”: socio-anthropological notes on finding out oneself HIV-positive - Agostini, Rafael; Maksud, Ivia; Franco, Tulio (Saúde e Sociedade, 2017)
During the almost four decades of the HIV/AIDS epidemic, its clinical administration has undergone considerable changes. The current temporal extension imposes on HIV+ subjects (re)positions in the agency of life and illness from the perspective of a long-term illness that suggests the adaptation of habits and behaviors, frequent interaction with health services and professionals and the continuous use of medicines - in addition to coexistence with the social, subjective and even physical impacts of the disease. The objective of this work is to discuss, based on data from a research carried out with young seropositive patients, the processes of disclosure of the diagnosis. Six interviews were opened in depth, from a triggering question, with youngsters between 18 and 22 years of age, from the popular strata and of both sexes and of mother-to-child transmission. The theoretical perspective that anchored our digressions was socio-anthropological. The results indicate that among these young people, normality appears as the structural axis of the diagnosis, which contrasts, among other things, with the fact that most interviewees prefer to keep their serology a secret. Family and service alternated as responsible for the revelation. In addition, activism appears as a way to find a place for serology in the course of life and as a strategy to deal with the routine after the diagnosis.